2016
DOI: 10.18632/oncotarget.14028
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis of urinary microbiota is positively correlated with Type 2 diabetes mellitus

Abstract: Type 2 diabetes mellitus (T2DM) may be associated with altered urinary microbiota in female patients. We investigated alterations of urinary microbiota in Chinese female T2DM patients, and explored the associations between urinary microbiota and a patient’s fasting blood glucose (FBG), urine glucose (UGLU), age, menstrual status, and body mass index (BMI). Midstream urine was collected from 70 female T2DM patients and 70 healthy females. Microbial diversity and composition were analyzed using the Illumina MiSe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 60 publications
8
46
0
Order By: Relevance
“…Three bands were identified as Proteobacteria and the other one band was Firmicutes. The occurrence of these bacterial phyla has also been reported previously in various studies by using either culture-dependent methods (Liu et al 2017). In our study, we observed bacterial isolates belong to Gammaproteobacteria, these included Shigella flexneri, Klebsiella sp., and Escherichia sp.…”
Section: The Diversity Of Bacteria Based On Metagenomic 16s Rrnatargesupporting
confidence: 86%
“…Three bands were identified as Proteobacteria and the other one band was Firmicutes. The occurrence of these bacterial phyla has also been reported previously in various studies by using either culture-dependent methods (Liu et al 2017). In our study, we observed bacterial isolates belong to Gammaproteobacteria, these included Shigella flexneri, Klebsiella sp., and Escherichia sp.…”
Section: The Diversity Of Bacteria Based On Metagenomic 16s Rrnatargesupporting
confidence: 86%
“…The most abundant phylum in both bladder cancer and healthy group was Firmicutes, followed by Actinobacteria, Bacteroidetes and Proteobacteria (Fig. 2), which is in good Also, inter-individual variability, observed between microbiomes of the participants in our study, has been repeatedly demonstrated in publications on urinary microbiome 10,11,19,20 , which makes it challenging to define what constitutes a 'core' bladder microbiome. Our comparison of bladder cancer versus healthy urine samples revealed bacterial taxa that 1 1 6 were overrepresented in one of the sample subgroups ( Fig.…”
Section: Introductionsupporting
confidence: 59%
“…In the past, urine was thought to be sterile in healthy individuals. Recent studies show that there are a great number of microorganisms in the urinary tract [1] and changes in patients with type 2 diabetes mellitus [2], overactive bladder syndrome [3,4], urinary incontinence, interstitial cystitis [5], neuropathic bladder [6,7], sexually transmitted infections [8], and chronic prostatitis/chronic pelvic pain syndrome [9,10].…”
Section: Introductionmentioning
confidence: 99%